Alterations of phenotype, physiology, and functional substances reveal the chilling-tolerant mechanism in two common Olea Europaea cultivars - Jiang, Chenkai; Hu, Wenjun; Lu, Hongling; Chen, Lin; Niu, Erli; Zhu, Shenlong; Shen, Guoxin (Frontiers in Plant Science, 2023)
Olive suffered from cold damage when introduced to high latitude regions from its native and warm-temperature area. This study, therefore, aims to improve the adaption of olive to the climate where is cold in a period of a year. The phenotype, physiological performance, the nutrient content and gene expression level of olive leaves (two widely planted cultivars) were detected after being cultivated under normal and cold stress conditions. The results showed that the cold-tolerant cultivar possessed stronger photosynthesis efficiency and higher anti-oxidase activity after cold treatment, compared to the cold-sensitive cultivar. Alteration of gene expression levels and metabolites in amino acid metabolism, glycerolipid metabolism, diterpenoid biosynthesis, oleuropein metabolism pathways played an important role in cold responses of olive. Furthermore, the network of genes for ubiquitination and metabolites were constructed, which suggested that poly ubiquitination makes the greatest contributions to stable physiology of olive under cold stress. It plays an important role in understanding cold hardiness of olive, and screening cold resistant varieties for excellent quality and yield.